Prevalence of intestinal parasites in dogs from São Paulo State, Brazil - Oliveira-Sequeira, TCG; Amarante, AFT; Ferrari, T. B.; Nunes, L. C. (Elsevier B.V., 2002)
The prevalence of gastrointestinal parasites in stray dogs, and dogs with owners was investigated by fecal examinations from 271 dogs employing sedimentation, simple flotation and centrifugation-flotation methods. The centrifugation-flotation method, when compared to simple flotation or sedimentation methods was generally more accurate in the diagnosis of all intestinal parasites, but statistical differences were detected only in relation to Giardia spp. and Cystoisospora spp. (synonym Isospora spp.). The following parasites, with their respective prevalence, were diagnosed in the fecal samples: Ancylostoma spp. (23.6%); Toxocara canis (5.5%); Trichuris vulpis (4.8%); Spirocerca lupi (1.9%); Dipylidium caninum (0.7%); Giardia spp. (12.2%); Hammondia heydorni (2.6%); Cystoisospora spp. (8.5%); and Sarcocystis spp. (2.2%). The prevalence of most parasites was similar for dogs of mixed-breed and for dogs of a defined-breed, except for Cystoisospora spp. and T canis which showed a significantly higher prevalence in mixed-breed dogs. The prevalence of Ancylostoma spp. (17.1%) was significantly lower in stray dogs than in those with an owner (31.9%) and the prevalence of Giardia spp. and Cystoisospora spp. was higher in stray dogs (P < 0.05). No effect of season on the occurrence of the different parasite genera could be observed, except for Ancylostoma spp., for which an increase in the percentage of dogs shedding eggs was observed at the beginning of Summer with a peak occurrence during April and May (Autumn). The prevalence of Ancylostoma spp., T canis, T vulpis, Giardia spp. and Cystoisospora spp. was higher in adult males than in adult females, but significant differences between the two groups occurred only with Giardia spp. Young animals were found to more frequently shed Nematode eggs in feces than adult animals. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: dog; intestinal parasites; prevalence; Giardia; Toxocara; Ancylostoma